2020
DOI: 10.47162/rjme.61.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary leiomyomatosis and renal cell cancer syndrome – case report and review of the literature

Abstract: Hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC) is an exceptionally rare autosomal dominant condition caused by a germline heterozygous mutation of the fumarate hydratase gene. It manifests as multiple piloleiomyomas, associated with numerous, early-onset uterine leiomyomas in female patients, as well as a highly increased risk of renal cell carcinoma (RCC), most often type 2 papillary RCC. HLRCC has been described in association with adrenal cortical hyperplasia, pheochromocytoma, adrenal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A total of 5 cases with HLRCC were found in the literature and these are summarized in Table 1 , which gives the patients' chief complaint, timing of hysterectomy or myomectomy, the clinical manifestation of HLRCC and the methods to confirm HLRCC. The first four patients (cases 1–4) underwent either hysterectomy or myomectomy and HLRCC was confirmed later by genetic testing [ 1 , 3 , 4 , 11 ]. These patients came back months or years later with other clinical manifestations of HLRCC and further workup helped confirmed the condition by histopathology and genetics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 5 cases with HLRCC were found in the literature and these are summarized in Table 1 , which gives the patients' chief complaint, timing of hysterectomy or myomectomy, the clinical manifestation of HLRCC and the methods to confirm HLRCC. The first four patients (cases 1–4) underwent either hysterectomy or myomectomy and HLRCC was confirmed later by genetic testing [ 1 , 3 , 4 , 11 ]. These patients came back months or years later with other clinical manifestations of HLRCC and further workup helped confirmed the condition by histopathology and genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient (case 5) had genetic testing before surgery since she presented with all the telltale signs of HLRCC and had a family history of the condition [ 12 ]. In most reports, the authors suggested using cutaneous leiomyomas as the primary indicator of HLRCC [ 1 , 3 , 4 , 12 ]. However, no case used uterine myomas as the only indicator in a young woman with suspected HLRCC after hysterectomy or myomectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are light brown protuberant nodules that measure approximately 1 cm. Although the symptoms are not obvious, these nodules on the skin can be painful under harsh environments, such as emotional stress and cold temperatures ( 110 - 112 ).…”
Section: Fh and Tumorsmentioning
confidence: 99%